Larkin/Larkinburg, Jackson County - Schofield, Brooke (Kansas State University, The Chapman Center for Rural Studies, 2011)
Larkinburg is a small, unincorporated hamlet that straddles the county line between Jackson County and Atchison County, Kansas. In its prime, Larkinburg had a population of about 200. The town was named after M.E. Larkin, who owned 160 acres of land outside of the main town strip on the Atchison County side of Larkin Avenue.1 Mr. Larkin moved to Kansas from Indiana in 1860 but the town was not officially settled until 1880.
Brooke Schofield, “Larkin/Larkinburg, Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/61.
Keywords: Atchison County; Jackson County; Kimball; Larkin; Larkinburg; St. Agatha's Catholic Church